Ultrathin solar cells with Ag meta-material nanostructure for light absorption enhancement. (15th May 2018) - Poursafar, Jafar; Bashirpour, Mohammad; Kolahdouz, Mohammadreza; Vakilipour Takaloo, Ashkan; Masnadi-Shirazi, Mostafa; Asl-Soleimani, Ebrahim
Highlights: Ultrathin solar cell and plasmonic structures are combined to obtain superior performance. Ag nanostructures were applied to a novel meta-material design to obtain high-efficiency. The 3D-FDTD were clearly showed 189.5% short-circuit current density enhancement. 154.8% light absorption enhancement over the whole solar spectrum was obtained. Abstract: The two major problems of conventional photovoltaic devices are their low conversion efficiencies and relatively high production cost. Lately, ultrathin film photovoltaics have been proposed to overcome the mentioned issues. However, the thin film solar cells have some weaknesses, and the main deficiency is their low light absorption, which is related to the reduced absorber thickness. Therefore, light management plans are needed for ultrathin solar cells to enhance their light absorption. Using plasmonic and more specifically the meta-material structures is one of the efficient techniques to manage and trap the incident light inside the active region of photovoltaics. Here, we have proposed an ultrathin Si solar cell with embedded meta-material nanostripes in which their positions were swept in x and z directions to acquire the optimum performance. The results show that the designed structure gives rise to 154.8% light absorption enhancement and 189.5% short-circuit current density enhancement over the solar spectrum compared to the reference conventional structure.